A multigene approach to determine the molecular phylogeography of Argiope mangal and Argiope dang (Araneae: Araneidae) and their genetic relationships with the Argiope aetherea species group. (December 2016) - Tan, Ji; Chan, Zi-Yang; Lim, Phaik-Eem; Koh, Joseph Kok-Hong; Yong, Hoi-Sen
Abstract: The genus Argiope represents a collection of morphologically diverse orb-weaving spiders with a cosmopolitan distribution. Argiope dang and A. mangal are two Southeast Asian species that share remarkably similar morphological characteristics congeneric to the A. aetherea species group. However, in previous investigations, molecular data have not been used for the taxonomic categorization of A. dang and A. mangal . Additionally, gene flow between populations of A. dang and of A. mangal in their natural habitats has not been adequately studied. In the present study, mitochondrial 16S, COI and COII markers were used in addition to the nuclear H3 gene to elucidate the relationships between A. dang, A. mangal and various congeners within the A. aetherea species group. The haplotype diversity of A. dang and A. mangal was also investigated. Based on our molecular results, the A. aetherea species group was composed of three genetic lineages: (i) [ A. dang - ( A. radon - A. picta )] - [ A. modesta - A. aetherea ]; (ii) A. mangal ; and (iii) [( A. jinghongensis - A. aetheroides ) - A. versicolor ]. Haplotype analyses revealed a lack of gene flow between A. mangal populations in Peninsular Malaysia and those in Singapore. Populations of A. dang showed isolation-by-distance throughout the range of the species from Laos to Singapore. In this study for the first time, genetic data of A. mangal were reported for specimens collected from its type locality, Singapore. Four new distribution records were also reported: A. dang in Peninsular Malaysia and Cambodia; A. modesta in Bali, Indonesia; and A. jinghongensis in Peninsular Malaysia. Highlights: The A. aetherea species group consists of three genetic lineages. Argiope mangal and A. dang are closely related to the A. aetherea species group. Gene flow is absent between A. mangal populations of Peninsular Malaysia and Singapore. Populations of A. dang exhibit isolation-by-distance throughout their distribution range.